(untitled) (XXI Century. Spanish Literature and Culture, 2005)
The study is articulated as an invitation to weigh the horizon of possibilities opened by the hermeneutic approach to the paratextual elements, which help us to demarcate relationships between the different actors who negotiate in the communicative processes of type literary through the prefaces of the works of Lucía Etxebarría.